Substance Use Disorder New Research Perspectives in the Diagnosis, Treatment, and Prognosis - Sampedro-Piquero, Patricia; Darío Moreno Fernández, Román; Zancada-Menéndez, Clara (IntechOpen, 2023)
Adolescent substance abuse is a problem worldwide. This book provides a comprehensive overview of this issue with a special focus on alcohol abuse. Chapters discuss the biological, social, and environmental risk factors of substance abuse in adolescents, behavioral and pharmacological interventions to prevent or reduce the negative effects of substance abuse, psychological disorders associated with drug abuse, and much more.